Two-dimensional current flow in stringed PV cells and its influence on the cell-to-module resistive losses - Guo, Siyu; Singh, Jai Prakash; Peters, Marius; Aberle, Armin G.; Wong, Johnson (Solar Energy, 2016)
In a c-Si wafer based photovoltaic (PV) module, the current generated in each solar cell must flow to the ribbons soldered onto its front and rear surfaces. Conventionally, a simplified current flow pattern is assumed in calculating the resistive power losses in the cell plane and the ribbons. However, it is found in this work that this approach leads to more than 30% overestimation for the resistive loss on the rear-side ribbons for a typical monofacial solar cell. This work uses a detailed two-dimensional network simulation, which accurately solves the current flow patterns in both cell surface planes. It is found from this work that the conventional approach is sufficiently accurate in the case of an H-pattern finger-busbar metallization scheme, but not with a full-area metallization pattern, as commonly used on the rear of silicon wafer solar cells. For a c-Si PV module using 3-busbar monofacial solar cells, the actual resistive loss on the rear metallization plane is only 67% of the value calculated conventionally. Also, 17% of the cell interconnection resistive loss comes from the rear metal sheet, which is often ignored. To correct the results of the conventional approach, we introduce correction factors for c-Si PV modules using monofacial cells. Using the correction factors we achieve a significantly better prediction of the module's fill factor. We apply this approach to explain why the fill factor gain from replacing full-size solar cells by halved cells in a c-Si PV module is higher for bifacial than for monofacial solar cells. Experimentally, we find a 1.7% relative fill factor increase for monofacial halved-cell PV module, and a 2.0% relative increase for bifacial halved-cell PV module. The simulation results agree quite well with the experimental results. Since the influence from the cell metallization pattern on the cell-to-module resistive loss has not been investigated before, this work can be very useful correction and compensation for established methods analysing the cell-to-module losses. It also offers the guideline for PV module optimization in terms of further reducing the resistive loss.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Bifacial cell; Crystalline silicon; Halved cells; PV module; Resistive loss; Silicon wafer solar cells